RELEVANSI MATERI AJAR AKIDAH DALAM MATA PELAJARAN PAI DAN BUDI PEKERTI DI SEKOLAH DENGAN MATERI MATA KULIAH AKIDAH PADA PROGRAM STUDI ILMU PENDIDIKAN AGAMA ISLAM UNIVERSITAS PENDIDIKAN INDONESIA - Maula Nisa Nur Azizah, - (2018)
Penelitian ini mengungkap sejauh mana materi ajar akidah pada mata pelajaran PAI dan Budi Pekerti di sekolah memiliki keterkaitan dengan materi ajar mata kuliah akidahdi Prodi IPAI UPI. Penelitian ini bertujuan untuk mengetahui ruang lingkup materi ajar akidah di semua jenjang pendidikan (SD, SMP, SMA), ruang lingkup materi mata kuliah akidah pada Prodi IPAI UPI, dan relevansi antara keduanya. Teori yang yang dijadikan landasan dalam penelitian adalah teori tentang PAI, kurikulum dan Profesionalisme guru. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif dan studi dokumentasi. Hasil penelitian didapatkan bahwa sebagian besar materi akidah yang diajarkan di sekolah relevan dengan materi mata kuliah akidah pada Prodi IPAI UPI, namun di antara materi tersebut ada yang diajarkan di sekolah tetapi tidak dipelajari secara mendetail pada mata kuliah akidah pada Prodi IPAI UPI, dan ada materi akidah yang tidak diajarkan di sekolah namun dipelajari pada mata kuliah akidah pada Prodi IPAI UPI.Penelitian ini diharapkan dapat menjadi masukan untuk bahan ajar perkuliahan sehingga relevan dengan bahan ajar PAI di sekolah.;-- This research reveals the extent to which the teaching material ofIslamic Foundation on the subjects of Islamic Religion of education and Characters at School has a material relevance to the subject matter of clumps of Islamic Foundationcourses at Science of Islamic Education Study Program at Indonesia University of Education.This study aims to determine the scope of teaching materials in all levels of education (elementary school, junior high school, senior high school), the scope of course materials of Islamic Foundationat Science of Islamic Education Study Program at Indonesia University of Education, and the relevance between the both. Theories used as the foundation in research are theory about Islamic Religion of education, curriculum and teacher's professionalism. This research uses qualitative approach with descriptive method and documentation study. The result showed that most of teaching materials of Islamic Foundationlearned at school is relevant to the subject course materials of Islamic Foundationat the Science of Islamic Education Study Program at Indonesia University of Education, but among of the materials there are learned at school but not learned detailed in the course materials of Islamic Foundation at the Science of Islamic Education Study Program at Indonesia University of Education, and there are teaching materials of Islamic Foundationnot learned at school but learned course materials of Islamic Foundationat Science of Islamic Education Study Program at Indonesia University of Education. This research is expected to be an suggestion for course material so it is relevant to teaching materials of Islamic Religion of education and Characters at school.